The association of air pollution and greenness with mortality and life expectancy in Spain: A small-area study. (February 2017) - de Keijzer, Carmen; Agis, David; Ambrós, Albert; Arévalo, Gustavo; Baldasano, Jose M; Bande, Stefano; Barrera-Gómez, Jose; Benach, Joan; Cirach, Marta; Dadvand, Payam; Ghigo, Stefania; Martinez-Solanas, Èrica; et al.
Abstract: Background: Air pollution exposure has been associated with an increase in mortality rates, but few studies have focused on life expectancy, and most studies had restricted spatial coverage. A limited body of evidence is also suggestive for a beneficial association between residential exposure to greenness and mortality, but the evidence for such an association with life expectancy is still very scarce. Objective: To investigate the association of exposure to air pollution and greenness with mortality and life expectancy in Spain. Methods: Mortality data from 2148 small areas (average population of 20, 750 inhabitants, and median population of 7672 inhabitants) covering Spain for years 2009–2013 were obtained. Average annual levels of PM10, PM2.5, NO2 and O3 were derived from an air quality forecasting system at 4 × 4 km resolution. The normalized difference vegetation index (NDVI) was used to assess greenness in each small area. Air pollution and greenness were linked to standardized mortality rates (SMRs) using Poisson regression and to life expectancy using linear regression. The models were adjusted for socioeconomic status and lung cancer mortality rates (as a proxy for smoking), and accounted for spatial autocorrelation. Results: The increase of 5 μg/m 3 in PM10, NO2 and O3 or of 2 μg/m 3 in PM2.5 concentration resulted in a loss of life in years of 0.90 (95% credibility interval CI: 0.83, 0.98), 0.13 (95% CI: 0.09, 0.17), 0.20 years (95% CI: 0.16, 0.24) and 0.64 (0.59, 0.70), respectively. Similar associations were found in the SMR analysis, with stronger associations for PM2.5 and PM10, which were associated with an increased mortality risk of 3.7% (95% CI: 3.5%, 4.0%) and 5.7% (95% CI: 5.4%, 6.1%). For greenness, a protective effect on mortality and longer life expectancy was only found in areas with lower socioeconomic status. Conclusions: Air pollution concentrations were associated to important reductions in life expectancy. The reduction of air pollution should be a priority for public health. Highlights: This ecological small-area study included mortality data for all Spain. PM10, PM2.5, NO2 and O3 were associated with increased mortality risk. A 5 μg/m 3 increase in PM10 was associated with a reduction of ten months of life. Greenness only showed a protective association for mortality in low SES areas.